Effect of event-by-event fluctuations on hydrodynamical evaluation of elliptical flow - Andrade,R. (2007)
Elliptic flow at RHIC is computed event-by-event with NeXSPheRIO. We show that when symmetry of the particle distribution in relation to the reaction plane is assumed, there is a disagreement between the true and reconstructed elliptic flows. We suggest a possible way to take into account the asymmetry and get good agreement between these elliptic flows.